2016
DOI: 10.1007/s10518-016-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of buried electrical cables: evidence-based repair rates and fragility functions

Abstract: The fragility of buried electrical cables is often neglected in earthquakes but significant damage to cables was observed during the 2010-2011 Canterbury earthquake sequence in New Zealand. This study estimates Poisson repair rates, similar to those in existence for pipelines, using damage data retrieved from part of the electric power distribution network in the city of Christchurch. The functions have been developed separately for four seismic hazard zones: no liquefaction, all liquefaction effects, liquefac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Principal causes of PGD [28] will be estimated in CIP-Cast-ES as follow: a) coseismic fault displacement in the near-fault area will be calculated via semi-empirical correlations as a function of the earthquake magnitude (e.g. the ones available from Petersen et al, 2011); b) landslides triggered by seismic shaking [29] -this capability will be included in CIPCast-ES as discussed in the Conclusion section of this paper); c) liquefaction, lateral spreading, and seismic settlement will be estimated in term of liquefaction potential index (LPI) that proved to be a good predictor for the damages induced on buried cables [30].…”
Section: Seismic Hazard Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…Principal causes of PGD [28] will be estimated in CIP-Cast-ES as follow: a) coseismic fault displacement in the near-fault area will be calculated via semi-empirical correlations as a function of the earthquake magnitude (e.g. the ones available from Petersen et al, 2011); b) landslides triggered by seismic shaking [29] -this capability will be included in CIPCast-ES as discussed in the Conclusion section of this paper); c) liquefaction, lateral spreading, and seismic settlement will be estimated in term of liquefaction potential index (LPI) that proved to be a good predictor for the damages induced on buried cables [30].…”
Section: Seismic Hazard Representationmentioning
confidence: 99%
“…Repair rate relationship for buried cables. Kongar et al [30] produced for the first time evidence-based repair rates for the prediction of damage to buried cables, processing and analysing the damaged caused to them by 2010-2011 Canterbury, New Zealand, earthquake sequence. The analysis showed that the fragility of buried cables is influenced more by liquefaction than by ground shaking, and that lateral spread can cause more damage than settlement alone.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…As far as adverse meteorological conditions are concerned, both the transmission and distribution systems have been adversely affected by water bomb causing flooding, extreme snowfall or windstorm, and overheating [1]. As an example, highvoltage overhead lines might be subjected to failure due to ice sleeves on conductors during snowfalls; medium-voltage overhead lines might be subjected to failure due to fall of trees during windstorms, while overheating can cause catastrophic failure of underground cables [4,5]. As an example, a clamorous case occurred in Auckland, New Zealand, in 1998 that involved the failure of four major underground cables due to overheating in the summer period.…”
Section: Introductionmentioning
confidence: 99%
“…When scholars of different disciplines study the vulnerability of power grid nodes, they often analyze from their own professional perspective, and the research focus varies. Some literature is concerned with the response of mechanical properties of electric power facilities to seismic activity and the capacity of the facilities to resist structural damage [3][4][5]. Some literature describes the functional modeling of electrical substations as a method of studying how earthquakes damage these structures.…”
Section: Introductionmentioning
confidence: 99%